Leven in de Middeleeuwen - Falter, Linda; Falter, Michael; Herrin, Judith; Le Roy Ladurie, Emmanuel, 1929-2023 (Leuven : Davidsfonds, 2000)
Overzicht van het dagelijks leven in al zijn facetten
Keywords: anno 500-1499.; Cultuurgeschiedenis; geschiedenis; Geschiedenis van Europa